Outcome of stroke patients receiving different doses of recombinant tissue plasminogen activator - Ong CT; Wong YS; Wu CS; Su YH (Dove Medical Press, 2017)
Cheung-Ter Ong,1,2 Yi-Sin Wong,3 Chi-Shun Wu,1 Yu-Hsiang Su1 1Department of Neurology, Chia-Yi Christian Hospital, 2Department of Nursing, Chung Jen Junior College of Nursing, Health Science and Management, 3Department of Family Medicine, Chia-Yi Christian Hospital, Chia-Yi, Taiwan Background and purpose: Intravenous recombinant tissue plasminogen activator (tPA) at a dose of 0.9 mg/kg body weight is associated with a high hemorrhagic transformation (HT) rate. Low-dose tPA (0.6 mg/kg) may have a lower hemorrhage rate but the mortality and disability rates at 90 days cannot be confirmed as non-inferior to standard-dose tPA. Whether the doses 0.7 and 0.8 mg/kg have better efficacy and safety needs further investigation. Therefore, this study is to compare the efficacy and safety of each dose of tPA (0.6, 0.7, 0.8, and 0.9 mg/kg body weight) and to investigate the factors affecting early neurological improvement (ENI) and early neurological deterioration (END).Methods: For this observational study, data were obtained from 274 patients who received tPA thrombolytic therapy in Chia-Yi Christian Hospital stroke unit. The tPA dose was given at the discretion of each physician. The definition of ENI was a >8 point improvement (compared with baseline) at 24 h following thrombolytic therapy or an improvement in the National Institutes of Health Stroke Score (NIHSS) to 0 or 1 toward the end of tPA infusion. The definition of END was a >4 point increase in NIHSS (compared with baseline) within 24 h of tPA infusion. The primary objective was to investigate whether 0.7 and 0.8 mg/kg of tPA have higher ENI rate, lower END rate, and better outcome at 6 months. Poor outcome was defined as having a modified Rankin Scale of 3 to 6 (range, 0 [no symptoms] to 6 [death]). The secondary objective was to investigate whether low-dose tPA has a lower risk of intracerebral HT than that with standard-dose tPA. We also investigated the factors affecting ENI, END, HT, and 6-month outcome.Results: A total of 274 patients were included during the study period, of whom 260 were followed up for >6 months. There was a trend for the HT rate to increase as the dose increased (P=0.02). The symptomatic HT rate was not significantly different among the low-dose and standard-dose groups. The ENI and END (P=0.52) were not significantly different among the four dosage groups. The clinical functional outcome at 6 months after stroke onset was poorer in the standard-dose group (P=0.02). Stroke severity (P<0.01), stroke type (P=0.03), and diabetes mellitus (P=0.04) affected the functional outcome at 6 months.Conclusion: Among the 274 patients receiving tPA thrombolytic therapy, the HT rate increased as dose increased. The symptomatic HT, ENI and END rates were not significantly different among the low-dose (0.6, 0.7, and 0.8 mg/kg) and standard-dose groups. Stroke severity (NIHSS >12), stroke type (cardioembolism and large artery atherosclerosis) and diabetes mellitus were associated with poor outcome at 6 months. Keywords: stroke, thrombolytic therapy, outcome, neurological deterioration, tissue plasminogen activator, thrombolysis